Imports and TFP at the Firm Level: The Role of Absorptive Capacity - Patricia Augier; Olivier Cadot; Marion Dovis (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
This paper estimates the effect of the decision to import intermediate goods and capital equipment on Total Factor Productivity (TFP) at the firm level on a panel of Spanish firms (1991-2002). We use two alternative approaches. In the first, we estimate TFP and apply a diff-in-diff estimator with a control group constructed by propensity-score matching. In the second, direct method, we estimate TFP with imported inputs as a state variable in one stage. Both approaches show that the effect of a firm's decision to source intermediates and capital equipment abroad on its TFP depends critically on its capacit y to absorb technology, measured by the proportion of skilled labor.
Keywords: F2; O1; O2; 330